Sigmoid volvulus with bowel ischemia secondary to adhesion and helminth - Azmi Ahmad; Lo, Zhen Zhen; Muhammad Yusuf Muharam (Elsevier Inc, 2024)
Sigmoid volvulus is a life-threatening cause of bowel obstruction. We presented a unique case of sigmoid volvulus leading to bowel ischemia secondary to adhesion and helminth coinfection in a 38-year-old female patient. She had a history of pulmonary tuberculosis and two previous lower-segment caesarean sections and bilateral tubal ligation. She was presented with a month’s history of progressive abdominal distension, followed by acute onset of lower abdominal pain, vomiting, and constipation. Radiological studies revealed a dilated sigmoid colon with features suggestive of volvulus and possible bowel ischemia. She underwent successful laparotomy and anterior resection, covering ileostomy. We highlight the importance of considering bowel obstruction complicated with bowel ischemia in patients presenting with acute abdominal symptoms and histories of previous abdominal surgeries, underscoring the role of timely surgical intervention in preventing fatal outcomes.